Pedagogical Content Knowledge on Early Mathematics Among Malaysia’s Preschool Teachers: A Literature Review - Seman, Norhaizian; Alias , Aliza X; Ikhsan, Zanaton (International Journal of Psychosocial Rehabilitation, 2020)
Early childhood education in Malaysia refers to the programmes provided for children from birth to the age of eight. The programmes include related activities from kindergarten, preschool, to primary Year Two. The National Preschool Standard Curriculum (NPSC) focuses on a student-centred learning curriculum. Such knowledge is necessary to enable preschool teachers to make teaching and learning a fun and meaningful experience for preschoolers in Malaysia. Improvement in the quality of teaching and learning (T&L) of preschool teachers is closely linked to the teachers’ PCK, which has the potential to enhance their teaching profession. The purpose of this paper is to explain the concepts and requirements of early mathematical PCK in a preschool education. The qualitative study is based on analysis of documents, journals, and books related to the discussions of PPK. The library methodology involves inductively and deductively analysing previous studies using Shulman’s model to identify early mathematical concepts and interests. The findings suggest that preschool teachers’ mastery of PCK can enhance their skills and understanding of early mathematics. The studies have also found that students who achieved excellent results at the primary or secondary level had basic mathematical learning from the preschool level. Such a trend needs to be addressed by the MoE and educators who are aware of the importance of early mathematics from preschool. This study is expected to shed light on the importance of improving the quality of preschool teachers’ delivery of early mathematics teaching.